ASSESS THE EFFECTIVENESS OF NURSING CARE ON PATIENTS WITH PRESSURE URTICARIA - R.RAMANI (International Journal of Pharma and Bio Sciences, 2016)
The study was conducted to evaluate the effectiveness of Nursing care on patients with pressure urticaria. Delayed Pressure Urticaria is considered a rare disease,with clinical diagnosis different from classical urticaria, with possible systemic manifestations. Therefore, it is frequently underdiagnosed, even by specialists. In this article, the case of a patient with a typical history of pressure-induced lesions is presented. Because the patient had fever and leukocytosis, she was admitted to a hospital for investigation of infection.Chronic urticaria is defined as episodic or daily hives lasting for at least 6 weeks and impairs quality of life. Two main subtypes include chronic idiopathic (spontaneous) urticaria and inducible (physical) urticaria, but some patients have urticarial vasculitis. “Autoimmune chronic urticaria” implies the presence of histamine releasing or mast cell activating autoantibodies to Ige or fceri, the high affinity receptor on mast cells and basophils. In patients not readily controlled with labeled dosages of second generation H1 receptor antagonists (antihistamines), there is evidence for reduction of urticaria using up to 4 fold increases in labeled dosages. The biologic modifier, omalizumab, helps to reduce lesions of chronic urticaria within 1–2 weeks.chronic urticaria has a wide spectrum of clinical presentations and causes. Still, despite our best efforts no cause may be found in the majority of cases. The treatment options are: Primary prevention in the form of avoidance of aggravating factors; counseling; antihistamines; leukotriene receptor antagonists; prednisolone; sulfasalazine and a host of immunosuppressives like methotrexate, cyclosporine, omalizumab etc..